Implementation of Civic Education Program to Form Student Character in Elementary Schools - Pratiwi, Wita (International Journal of Students Education, 2024)
This study aims to explore the implementation of the Citizenship Education Program (PKn) at the elementary school level as an effort to shape students' character. Utilizing a literature review method, this research analyzes various sources, including scholarly articles, books, and relevant journals related to citizenship education and character development. The findings indicate that citizenship education plays a crucial role in instilling moral and ethical values in students, including the values of Pancasila, which is the foundational philosophy of Indonesia. The Civics program focuses not only on academic aspects but also on character formation through interactive and participatory learning activities. In this context, students are encouraged to understand their rights and responsibilities as citizens, as well as the importance of tolerance, justice, and social responsibility. However, the study also identifies several challenges in implementing Civics in elementary schools, such as insufficient teacher training, limited educational resources, and a lack of awareness among parents and the community regarding the importance of character education. The research concludes that to enhance the effectiveness of the Civics program in shaping students' character, collaboration among schools, parents, and the community is essential. Additionally, developing a more innovative and relevant curriculum that meets students' needs is crucial. Thus, citizenship education can significantly contribute to forming a generation of young individuals with strong character who are prepared to face future challenges.